Educaç\~ao e o rendimento dos ricos no Brasil - Marcelo Medeiros; Juliana Castro Galv\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– We examine the extent to which education is a main determinant of affluence in Brazil. We focus on workers in the top 1% of the labor earnings distribution. We use university courses data from the Sample Questionnaire of the 2010 Census. Our main conclusion is that while education may be important to explain total inequality, there is no evidence that mass education is a major factor explaining the differences between the rich and the rest of the population. Not even elite education can be assumed to be a main determinant of the current levels of affluence. Consequently, an important part of total inequality cannot be reduced by educational policies.
Keywords: D31; E24; I24; N36; J24; J31; J44; O15; O54; 330; social stratification; income inequality; rich; affluence; education; wage inequality